Three‐Layer Structured SnO2@C@TiO2 Hollow Spheres for High‐Performance Sodium Storage - Tian, Yu; Hu, Ping; Zhu, Ting; Liu, Zhenhui; Hu, Guangwu; Cai, Congcong; Jian, Zelang; Zhou, Liang; Mai, Liqiang (Energy & environmental materials (Hoboken, N.J.), 2021)
The unsatisfactory conductivity and large volume variation severely handicap the application of SnO2 in sodium‐ion batteries (SIBs). Herein, we design unique three‐layer structured SnO2@C@TiO2 hollow spheres to tackle the above‐mentioned issues. The hollow cavity affords empty space to accommodate the volume variation of SnO2, while the C and TiO2 protecting shells strengthen the structural integrity and enhances the electrical conductivity. As a result, the three‐layer structured SnO2@C@TiO2 hollow spheres demonstrate enhanced Na storage performances. The SnO2@C@TiO2 manifests a reversible capacity two times to that of pristine SnO2 hollow spheres. In addition, Ex situ XRD reveals highly reversible alloying and conversion reactions in SnO2@C@TiO2 hollow spheres. This study suggests the introduction of a hollow cavity and robust protecting shells is a promising strategy for constructing SIB anode materials. Unique three‐layer structured SnO2@C@TiO2 hollow spheres are designed to tackle the low electrical conductivity and large volume expansion issues of SnO2. The as‐designed SnO2@C@TiO2 hollow spheres demonstrate improved Na storage performances.